2014
DOI: 10.1109/tasc.2013.2284548
|View full text |Cite
|
Sign up to set email alerts
|

Passive Shimming for Magic-Angle-Spinning NMR

Abstract: Abstract-The superconducting dipole magnets wound with HTS wires have been developed for a magic-angle-spinning NMR. The magnetic field of the dipole magnets is tilted from z-axis. Since the highly homogeneous magnetic field is required, the magnetic field of the dipole magnets is necessarily compensated by passive and/or active shimming. However, the compensation of all the components has not been reported. Usually, due to the axial symmetry of a solenoid magnet, only z component of the magnetic field is homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…13,[16][17][18]21,22 The spherical harmonic coefficients presented in this paper facilitate active shimming for various kinds of coils by eliminating the higher terms of the entirecomponent coefficients than the 0th one. On the other hand, in the case of passive shimming, it is difficult to eliminate the higher terms of the coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[16][17][18]21,22 The spherical harmonic coefficients presented in this paper facilitate active shimming for various kinds of coils by eliminating the higher terms of the entirecomponent coefficients than the 0th one. On the other hand, in the case of passive shimming, it is difficult to eliminate the higher terms of the coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…The passive shimming is done by combining the magnetic moment method with an optimization method. 22 Recently, a few magnets are designed to generate a magnetic field tilted from the z-axis. The forms of the spherical harmonic coefficients presented in this paper and the previous ones 4-17 cannot be easily used for shimming design computation.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been conducted in ferromagnetic and active shimming of a solenoidal (z-axis) NMR magnet [7]-[11]. Additionally, previous research has shown ferromagnetic shimming algorithms for the magic-angle magnet [12]-[14]. …”
Section: Introductionmentioning
confidence: 99%